High-resolution shotgun proteomics reveals that increased air [CO2] amplifies the acclimation response of coffea species to drought regarding antioxidative, energy, sugar, and lipid dynamics - Marques, Isabel (2022)
This work received funding support from the European Union's Horizon 2020 research and innovation program (grant agreement No 727934 , project BreedCAFS), ( CEF ), - Individual Call (CEEC Individual) - 2021.01107.CEECIND/CP1689/CT0001 (IM) . Fellowships from the Conselho Nacional de Desenvolvimento Científico e Tecnológico, Brazil (CNPq) , (to F.M. DaMatta and F.L. Partelli), and Fundação de Amparo à Pesquisa do Estado de Minas Gerais, Brazil (FAPEMIG, projects CRA-RED-00053-16 and APQ 01512-18 , to F.M. DaMatta) are also greatly acknowledged. Publisher Copyright: © 2022 Elsevier GmbH